Clinicopathological features and evaluation of microsatellite stability of colorectal carcinoma with cribriform comedo pattern - Tuğba Günler; Pinar Karabağli; Hicret Tiyek; Özge Keskin; Muslu K. Körez (Indian Journal of Pathology and Microbiology)
Background: Cribriform comedo-type adenocarcinoma (CCA) was a colon cancer subtype defined in the 2009 World Health Organization (WHO) classification. In the 2018 classification, it was a colon cancer subtype included in the adenocarcinoma, Not otherwise specified (NOS) group. A few studies have reported that colon cancers with a cribriform pattern have worse overall survival, and most of them are microsatellite stable (MSS). In this study, we evaluated CCAs based on their clinicopathologic features and microsatellite stability. We aimed to answer whether these tumors could be defined as a distinct morphologic subtype with prognostic significance. Materials and Methods: Pathology reports and specimens from 449 patients with colorectal adenocarcinoma (CRA) were re-evaluated. All subtypes were determined. To evaluate MSS status, the CCA cases were immunohistochemically stained with anti-MLH1, MSH2, MSH6, and PMS2 antibodies. Results: CCA was present in 40.5% of cases. These cases were found to have higher rates of lymph node metastasis, lymphovascular-perineural invasion, metastasis, and advanced stage (P < 0.05). Also, 2.7% of CCA cases were microsatellite instable (MSI). However, no statistically significant result was found regarding overall survival and progression-free survival of CCA cases with MSI. Conclusion: According to the findings, CRAs with comedo cribriform patterns are tumors with more aggressive features. It can be said that these tumors have a specific molecular feature related to MSS. Because this feature is important for planning adjuvant chemotherapy, it may be useful to identify cases, particularly with a cribriform comedo pattern >90%. However, because no significant difference in survival rates was found, CCAs may not need to be defined as distinct subtypes.